A viabilidade da educação profissional integrada ao ensino médio como instrumento de efetividade da gestão pública voltada ao Centro de Atendimento Socioeducativo de Santa Maria/RS - Trindade, Valesca Azevedo (2023)
The research problem of this study was to answer the following question: what are the necessary procedures for the feasibility of integrating vocational education into high school as an instrument of effectiveness in public management, aimed at adolescents who are serving a socio-educational measure with the Socio-Educational Service Center of Santa Maria/RS? As a general objective, we tried to present the viability of professional education integrated into high school as an instrument of effectiveness in public management aimed at adolescents who are serving socioeducational measures with the Socio-Educational Assistance Center of Santa Maria/RS. Specifically, the aim was to: analyze the Political and Pedagogical Project of the school linked to the Socio-Educational Service Center of Santa Maria/RS and the existing policies in the legal frameworks; demonstrate the current model of education offered to adolescents who are serving socio-educational measures at the Socio-Educational Service Center in Santa Maria/RS; and identify support networks with a view to establishing a partnership with public education institutions. This research was characterized as exploratory, with a mixed questionnaire. Data were obtained through bibliographical and documental survey and development of questionnaires. And at the end of the research, it should be noted that, a product was made possible that seeks to promote Socio-educational Integrated High School for adolescents deprived of freedom, based on the studies of Araújo and Silva (2017), which has seven steps as a script: 1) understanding of the EMI and Sinase policy; 2) continued training of professionals; 3) guarantee spaces for effective participation; 4) investing in the integration of people and knowledge; 5) democratic culture/democratic management; 6) the role of education managers in building the EMI of the Network; and 7) expanding and encouraging student participation.